Predation and caribou populations - Seip, Dale R. (Rangifer, 1991)
Predation, especially wolf (Canis lupus) predation, limits many North American caribou (Rangifer tarandus) populations below the density that food resources could sustain. The impact of predation depends on the parameters for the functional and numerical response of the wolves, relative to the potential annual increment of the caribou population. Differences in predator-avoidance strategies largely explain the major differences in caribou densities that occur naturally in North America. Caribou migrations that spatially separate caribou from wolves allow relatively high densities of caribou to survive. Non-migratory caribou that live in areas where wolf populations are sustained by alternate prey can be eliminated by wolf predation.